UNIFIED BESSEL, MODIFIED BESSEL, SPHERICAL BESSEL AND BESSEL-CLIFFORD FUNCTIONS - Yasar, Banu Yilmaz; Ozarslan, Mehmet Ali (Univ Prishtines, 2016)
In the present paper, unification of Bessel, modified Bessel, spherical Bessel and Bessel-Clifford functions via the generalized Pochhammer symbol [H. M. Srivastava, A. cetinkaya and 0. Kiymaz, A certain generalized Pochhammer symbol and its applications to hypergeometric functions, Applied Mathematics and Computation, 2014, 226 : 484-491] is defined. Several potentially useful properties of the unified family such as generating function, integral representation, Laplace transform and Mellin transform are obtained. Besides, the unified Bessel, modified Bessel, spherical Bessel and Bessel-Clifford functions are given as a series of Bessel functions. Furthermore, recurrence relations and partial differential equation of the so-called unified family are found. Moreover, the Mellin transform of the products of the unified Bessel functions are obtained. Besides, a three-fold integral representation is given for unified Bessel function. Some of the results which are obtained in this paper are new and some of them coincide with the known results in special cases.
Keywords: Generalized Pochhammer symbol; generalized Bessel function; generalized spherical Bessel function; generalized Bessel-Clifford function